Local fisher knowledge reveals changes in size of blue swimmer crabs in small-scale fisheries. (September 2022) - Obregón, Clara; Christensen, Joseph; Zeller, Dirk; Hughes, Michael; Tweedley, James R.; Gaynor, Andrea; Loneragan, Neil R.
Abstract: Fisheries stock status is generally based on time series catch and effort data sourced from independent surveys and the fishery. These methods are often expensive and can be limited temporally and spatially. Alternative methods include the use of local fisher knowledge (LFK) to identify observed changes in catch. The blue swimmer crab ( Portunus armatus ) supports a small-scale commercial fishery and one of the most popular recreational fisheries in south-western Australia. Previous studies identified concerns from recreational fishers over its long-term sustainability. To understand if fishers' perceptions of change provide useful information on actual changes in the fisheries, a triangulation approach was used to assess changes in size and abundance of crabs in two estuaries (Peel-Harvey and Swan-Canning). Three types of data were used: (i) fisher recollections from 1940s to 2010s, including face-to-face interviews and online surveys; (ii) historical records from newspaper articles from 1900 to 2000; and (iii) quantitative data on size between 2006/07 and 2018/19. Results identified: (i) crabs were smaller in the Peel-Harvey, a consistent difference identified in all data sources; (ii) crab size was perceived to have decreased in the Peel-Harvey; (iii) inter-generational differences in fishers' perceptions regarding size changes over time; and (iv) historical evidence of persistent fishers' concerns and perceptions of changes in the fishery and wider environment. These findings are evidence of a likely decline in the average size of crabs in south-western Australia over the last century, particularly in the Peel-Harvey, and demonstrate that LFK may be a valuable source of information particularly when other data sources are lacking. Graphical Abstract: ga1